2024
DOI: 10.1097/ju.0000000000003891
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Therapy for Prostate Cancer: AUA/ASTRO/SUO Guideline Part II: Treatment Delivery for Non-metastatic Biochemical Recurrence After Primary Radical Prostatectomy

Todd M. Morgan,
Stephen A. Boorjian,
Mark K. Buyyounouski
et al.

Abstract: Conclusions: Optimizing and personalizing the approach to salvage therapy remains an ongoing area of work in the field of genitourinary oncology and represents an area of research and clinical care that requires wellcoordinated, multi-disciplinary efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“… 3 Therefore, guidelines established from a collaboration among the American Urology Association, American Society for Radiation Oncology and Society of Urologic Oncology recommend androgen‐deprivation therapy, in addition to salvage radiation therapy, for patients with biochemical recurrence (BCR) after RP who have persistent PSA. 4 In a recent review article, the incidence of persistent PSA ranged between 3.1% and 34.6%, with a median of 11.0%. 2 Previous studies have shown that several clinicopathological variables, such as the D'Amico risk (high risk vs. medium and low risk), postoperative International Society of Urologic Pathology (ISUP) grade group ≥4, pathological T stage ≥pT3, extraprostatic extension (EPE), seminal vesicle invasion (SVI), positive surgical margins (PSMs) and lymphovascular invasion (LVI), were independently associated with persistent PSA after robot‐assisted RP (RARP).…”
Section: Introductionmentioning
confidence: 99%
“… 3 Therefore, guidelines established from a collaboration among the American Urology Association, American Society for Radiation Oncology and Society of Urologic Oncology recommend androgen‐deprivation therapy, in addition to salvage radiation therapy, for patients with biochemical recurrence (BCR) after RP who have persistent PSA. 4 In a recent review article, the incidence of persistent PSA ranged between 3.1% and 34.6%, with a median of 11.0%. 2 Previous studies have shown that several clinicopathological variables, such as the D'Amico risk (high risk vs. medium and low risk), postoperative International Society of Urologic Pathology (ISUP) grade group ≥4, pathological T stage ≥pT3, extraprostatic extension (EPE), seminal vesicle invasion (SVI), positive surgical margins (PSMs) and lymphovascular invasion (LVI), were independently associated with persistent PSA after robot‐assisted RP (RARP).…”
Section: Introductionmentioning
confidence: 99%